2003
DOI: 10.1210/me.2003-0056
|View full text |Cite
|
Sign up to set email alerts
|

The Formin Family Protein, Formin Homolog Overexpressed in Spleen, Interacts with the Insulin-Responsive Aminopeptidase and Profilin IIa

Abstract: Insulin stimulates translocation of glucose transporter isoform type 4 (GLUT4) and the insulin-responsive aminopeptidase (IRAP) from an intracellular storage pool to the plasma membrane in muscle and fat cells. A role for the cytoskeleton in insulin action has been postulated, and the insulin signaling pathway has been well investigated; however, the molecular mechanism by which GLUT4/IRAP-containing vesicles move from an interior location to the cell surface in response to insulin is incompletely understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…TLR9 are retained, we screen for cytoskeletal proteins that might interact with IRAP and could interfere with endosomal motility. Indeed, considering that the cytosolic tail of IRAP was shown to interact with two cytoskeleton components, an actin nucleation factor, the formin FHOD1 20 and the intermediate filament vimentin 19 , we hypothesized that these interactions ensure the anchoring of IRAP and TLR9 endosomes to cytoskeleton. Whereas the interaction of IRAP with vimentin was not detectable in DCs (experiments not shown), we found that IRAP binds to FHOD4 formin.…”
Section: ! Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR9 are retained, we screen for cytoskeletal proteins that might interact with IRAP and could interfere with endosomal motility. Indeed, considering that the cytosolic tail of IRAP was shown to interact with two cytoskeleton components, an actin nucleation factor, the formin FHOD1 20 and the intermediate filament vimentin 19 , we hypothesized that these interactions ensure the anchoring of IRAP and TLR9 endosomes to cytoskeleton. Whereas the interaction of IRAP with vimentin was not detectable in DCs (experiments not shown), we found that IRAP binds to FHOD4 formin.…”
Section: ! Disscussionmentioning
confidence: 99%
“…The regulated trafficking of IRAP depends on the cytosolic domain of the enzyme, which has been shown to interact with several proteins involved in vesicle formation or in cytoskeleton remodeling, such as the golgin p115 18 , vimentin 19 and FHOS (formin homologue overexpressed in the spleen, also called FHOD1) 20 . Whether these proteins and their interaction with the cytosolic domain of IRAP play a role in the trafficking of IRAP + endosomes is not known.…”
mentioning
confidence: 99%
“…IRAP being a membrane protein that contains two dileucine motifs with a preceding acidic cluster ( 40 EPDEVEYEPRGSRLL 54 , 64 DEDEEDYESSAKLL 77 ), injection of the IRAP55-82 induced GLUT4 translocation in 3T3-L1 adipocytes, suggesting that IRAP interacts with a sorting and targeting protein regulating GLUT4 translocation (10)(11)(12). IRAP55-82 has also been shown to associate with acyl-coenzyme A dehydrogenase (13) and formin homolog over-expressed in spleen (14). Furthermore, IRAP1-109 has been shown to interact with p115 (15), and a defined sequence ( 96 RQSPDG 101 ) has been shown to be involved in binding to the ankyrin repeats of tankyrase (16).…”
Section: Irap Of Residue 1-49 Is the Major Site Of Tbc1d4 Ptb2 Interamentioning
confidence: 99%
“…Formins are critical for cytokinesis, for the establishment of cell polarity and for control of morphogenesis. FHOS, a human formin first identified in a spleen library has been shown to interact with the small GTPase Rac1, to bind the actin binding protein profilin IIa and to activate the serum response transcription factor in vitro (Tojo et al, 2003;Westendorf, 2001). Recent studies indicate that FHOS can interact with actin monomers and may play a role in the regulation of cell motility and vesicle recycling as well (Koka et al, 2003;Tojo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%